A pátria sem fronteiras: imigração italiana na ficção de Fidélis Dalcin Barbosa - Maciel, Marcele Brusa (My University, 2014)
Study of the fictional works Semblantes de pioneiros and Campo dos Bugres, from author Fidélis Dalcin Barbosa. Analysis about the aspects regarding the social organization of the italian immigrants in Rio Grande do Sul: family, religion and work. Interdisciplinary confrontation with sociological and historiography facts about the immigration phenomenon. Fictional representation problematization built of doctrinaire and ethnocentric principles, which reinforce the heroic character of the italian immigrant.
Estudo das obras ficcionais Semblantes de pioneiros e Campo dos Bugres, de Fidélis Dalcin Barbosa. Análise de aspectos referentes à organização social dos imigrantes italianos no Rio Grande do Sul: família, religião e trabalho. Confrontação interdisciplinar com dados sociológicos e historiográficos acerca do fenômeno da imigração. Problematização da representação ficcional estruturada a partir de princípios doutrinadores e etnocêntricos que reforçam o caráter heróico do imigrante.
Keywords: Literatura brasileira; Imigração italiana; Cultura regional; Fidélis Dalcin Barbosa; Literatura sul-rio-grandense; Crítica literária; Italian immigration; Regional culture; Fidélis Dalcin Barbosa; Sul-rio-grandense literature; Literary criticism